Nostalgia, anomia and the fear of crime - Hirtenlehner, Helmut (Journal of criminology, 2025)
In times of change, individuals may feel disoriented and alienated, be afraid of crime and long for a supposedly better past. Despite these interdependencies, the interrelationships between anomia, nostalgia and fear of crime have remained under-researched. In order to close this gap, the current study investigates whether feelings of nostalgia increase fear of crime and what role sentiments of anomia might play in this context. The results of a university student survey in Austria indicate that both nostalgia and anomia affect the levels of fear of crime reported, and that the influence of sentiments of anomia on worry about crime is partially mediated by feelings of nostalgia. Instrumental variables analyses, employed to defuse the endogeneity issue, confirm the nostalgia effect.